Ensuring the Security of Onshore and Offshore Wind Farms in the Context of War or Terrorism - Ivanov, Glib; Poita, Yurii (Sustainable Marine Structures, 2025)
Traditional fossil fuels powerplants and their supply logistics are easy targets compared to renewables – therefore renewable energy is paramount to securing energy resilience. While wind farms exhibit vulnerabilities, they provide a great measure of power generation distribution across a vast area. This paper analyses the problems of ensuring the security of wind power plants (both onshore and offshore) in relation to military threats – missile and aviation strikes, sabotage or cyber-attacks. The article is based on the study of cases of damage to wind power plants, an analysis of their vulnerable points, and computer modelling using the AQWA diffraction motion response analysis program. The research has shown that wind power plants have some vulnerable points. Onshore installations being structurally more resistant to potential military strikes, and their cables are already hidden underground. Offshore turbines, particularly floating, exhibit more vulnerabilities: their cables and substations are easy targets and could be attacked without open war declaration, making them susceptible to terrorism. Particularly floating wind turbines’ mooring lines and cables already often fail naturally, making them easy targets for sabotage. The cost of currently available risk mitigation measures ranges from 6.71% of total wind farm cost for land-based turbines to 12.72% for a floating wind farm. Additional technological and organisational measures should be implemented to increase the resilience of wind power systems in times of war. These solutions must be cost-effective to justify their deployment in times of peace. ER